Gender Performance in the Kitchen of Indonesian Middle-Class - Lale Garjita Kusumaring Puji; Joko Adianto; Rossa Turpuk Gabe (International Journal of Built Environment and Scientific Research, 2023)
This paper explores gender performance in Indonesia's middle-class’ kitchen. Gender mainstreaming and gender responsiveness have been on the Indonesian national development agenda since 2000, especially in vertical housing. However, gaps in the publication of the policy's implementation indicate the need for a basic understanding of gender to specify what should be accommodated to fulfil the agenda. Moreover, in previous studies, gender in Indonesia has not been discussed in the context of gender relations within the household. This research answers the question regarding the performance of daily activities that took place in the kitchen based on the actors’ gender. The performativity is influenced by the fulfilment of their preferences based on their household type; consisting of individual, traditional, and non-traditional household types. Each household has its own type of kitchen that will maintain the performativity of the gender.